An Analysis of the Monologue Drama Script "Setan Hadir Tepat Waktu" by Bode Riswandi Using a Feminist Approach - Indra Setiawan; Khiyaroh, Neng Nihlah; Prasanti, Frita Dwi; Wahyuni, Dea Siti; Hopipah, Opi; Farras, Safwan Raihan; Putra, Adita Widara (Jurnal Bahasa Indonesia Prima (BIP), 2025)
This research aims to analyze Bode Riswandi's monologue drama, “Satan Comes on Time,” through the lens of feminist theory. The play tells the story of a marginalized woman who works as a sex worker and voices her inner struggle and social criticism of stigma, gender inequality, and the patriarchal system. This research employs a qualitative method with a descriptive-analytical approach, focusing on the representation of women, power relations, and social criticism in the text. The results of the analysis show that this text has five main elements of feminism, which are rooted in feminist theory, namely stereotypes of women, unequal power relations, reflective consciousness of female characters, the metaphor of the “devil” as a symbol of capitalism and patriarchy, and criticism of inequality in access to education and employment. Through this monologue, the voices of women who are often silenced appear as a narrative of resistance that touches and opens space for awareness of the importance of gender justice.